(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Sustainable and environmentally friendly interior design practices have grown in popularity in recent years. The field of interior architecture has adopted a fresh perspective in its design process. Consideration of both the user’s and the environment’s well-being are central to sustainable interior design. Sustainable interior design is discussed in the article, along with the significance and use of certain materials. In addition, examples of completed projects that prioritize environmental friendliness are shown, along with the fundamental principles of sustainable design. As a result of the economy’s meteoric rise, "green ecology" has quickly gained widespread acceptance. Investigating and studying the potential uses of biodegradable materials in this setting is worthwhile. The use of biodegradable materials in home decor is the topic of this article. Avoidance, reduction, and reuse are the three main tenets of waste minimization initiatives.